Blood of the tiger : a story of conspiracy, greed, and the battle to save a magnificent species - Mills, Judy A. (Boston : Beacon Press, 2015)
"Blood of the Tiger takes readers on a wild ride to save one of the world's rarest animals from a band of Chinese billionaires. Despite the tiger's beloved status, there may be fewer than three thousand left in the wild. At the same time, at least five thousand "domesticated" tigers have been reared on farms in China, not for traditional medicine but for the production of tiger-bone wine, tiger-skin decor, and gourmet cuisine enjoyed by the country's elite. J.A. Mills spent twenty years investigating the illicit wildlife trade and trying to stop the plot that threatens to transform this regal animal from jungle monarch into no more than a livestock commodity. In this memoir of geopolitical intrigue, Mills and a host of people she counts as heroes try to thwart a Chinese cadre's plan to launch billion-dollar industries banking on the extinction of not just wild tigers but also elephants and rhinos. Her journey takes her across Asia, into the jungles of India and Nepal, to Russia and Africa, traveling by means from elephant back to presidential motorcade, in the company of man-eaters, movie stars, and world leaders. Set against the backdrop of China's reawakening and ascendance to world dominance, Blood of the Tiger tells of a global fight to rein in the forces of greed on behalf of one of the world's most endangered species"--
"Trying to sidetrack J.A. Mills from her investigation of China's bear farms, her Communist Party minders take her to a rural mink farm to see a handful of tigers behind bars. That detour leads her to discover a conspiracy so pervasive that it threatens to take out every last tiger in the wild. In this memoir of geopolitical intrigue, the author tries to thwart a Chinese cadre's plan to make The King of the Jungle into a farm animal, to drive a billion-dollar luxury-goods industry. Her efforts take her across Asia and Europe, by every means from elephant back to presidential motorcade, and into the company of man-eaters, movie stars and world leaders. Every time victory seems at hand, powerful forces banking on the tiger's extinction intervene. Blood of the Tiger is a startling tale of human tenacity and greed, set against the backdrop of China's reawakening and ascendency toward world dominance"--
The thrall of the wild -- The promise -- Finding the man with the keys -- Prescription rewritten -- Intermission I. The wild ones -- Crouching dragon selling tigers -- Tiger Lily and and the art of war -- Off to see the wizard -- The Vladimir Putin show -- Intermission II. In the valley of the shadow -- Sino-US cat fight -- Hidden in plain sight -- The empire strikes back -- Hope for a tiger spring -- Epilogue -- How you can help end tiger trade.
Includes bibliographical references and index.
1 2
Keywords: Tiger trade -- China; NATURE -- Animals -- Big Cats; NATURE -- Endangered Species; NATURE -- Environmental Conservation & Protection; Tiger trade; China; China; China